Intravenous Fibrinolysis for Central Retinal Artery Occlusion: A Cohort Study and Updated Patient-Level Meta-Analysis. Issue 7 (July 2020) - Mac Grory, Brian; Nackenoff, Alex; Poli, Sven; Spitzer, Martin S.; Nedelmann, Max; Guillon, Benoit; Preterre, Cécile; Chen, Celia S.; Lee, Andrew W.; Yaghi, Shadi; Stretz, Christoph; Azher, Idrees; et al.
Abstract : Background and Purpose: Central retinal artery occlusion results in sudden, painless, usually permanent loss of vision in the affected eye. There is no proven, effective treatment to salvage visual acuity and a clear, unmet need for an effective therapy. In this work, we evaluated the efficacy of intravenous tissue-type plasminogen activator (IV alteplase) in a prospective cohort study and an updated systematic review and meta-analysis. Methods: We enrolled consecutive patients with acute central retinal artery occlusion within 48 hours of symptoms onset and with a visual acuity of <20/200 from January 2009 until May 2019. The primary outcomes were safety and functional visual acuity recovery. We compared rates of visual recovery between those treated with alteplase within 4.5 hours of symptom onset to those who did not receive alteplase (including an analysis restricted to untreated patients presenting within the window for treatment). We incorporated these results into an updated systematic review and patient-level meta-analysis. Results: We enrolled 112 patients, of whom 25 (22.3% of the cohort) were treated with IV alteplase. One patient had an asymptomatic intracerebral hemorrhage after IV alteplase treatment. Forty-four percent of alteplase-treated patients had recovery of visual acuity when treated within 4.5 hours versus 13.1% of those not treated with alteplase ( P =0.003) and 11.6% of those presenting within 4 hours who did not receive alteplase ( P =0.03). Our updated patient-level meta-analysis of 238 patients included 67 patients treated with alteplase within 4.5 hours since time last known well with a recovery rate of 37.3%. This favorably compares with a 17.7% recovery rate in those without treatment. In linear regression, earlier treatment correlated with a higher rate of visual recovery ( P =0.01). Conclusions: This study showed that the administration of intravenous alteplase within 4.5 hours of symptom onset is associated with a higher likelihood of a favorable visual outcome for acute central retinal artery occlusion. Our results strongly support proceeding to a randomized, placebo-controlled clinical trial. Abstract : Supplemental Digital Content is available in the text.